Nutrient balance in a constructed wetland system using treated domestic wastewater on ornamental sunflower crops - Cruz Magaña, Jazmin Del Carmen de la (2022)
This study aimed to assess the nutrient dynamics of raw and treated wastewater (RWW and WW) in constructed wetlands (CW) for the irrigation of ornamental sunflowers, compared to freshwater (Fw) in Red Yellow Latosol (RYL) with (OF) and without (WF) inorganic fertilization. The study was carried out from July 10th to October 2nd of 2019. Wastewater was applied in pots with 10 kg of RYL. The amount of salts in the RWW, influent and effluent of CW and UnS (Uncultivated System), were evaluated in eleven samples. The study also assessed the following: plant height (PH), stem diameter (SD), number of leaves (NL), leaf area index (LAI), the inner diameter of the capitulum (IDc), the outer diameter of the capitulum (ODc), number of petals in the bud (NP), days after harvest (DAH), fresh phytomass in the aerial part (FPAP), dry phytomass in the aerial part (DPAP), fresh phytomass of the capitulum (FPc), dry phytomass of the capitulum (DPc), nutrient content in the aerial sunflower, and chemical composition in the RYL. The average removal efficiency of K+, Ca2+, and Fe in the CW was 34.33, 37.88, 39.82, and 45.40%, respectively. The PH (86.54 cm), SD (11.75 mm), NL (21), and LAI 3646.73 cm2) were higher in the WWOF treatment at 70 days after sowing. Treated wastewater without fertilization (WWWF) presented higher P, K, S, B, and Mn absorption. Freshwater with fertilization accumulated greater amounts of N, and WWOF accumulated greater amounts of Zn. Wastewater increased the P content and decreased K+ and Ca2+ in RYL. Irrigation with domestic WW in CW provided salts to the soil and increased the growth and quality of sunflowers irrigated with Fw.